2022
DOI: 10.1108/jeas-11-2021-0222
|View full text |Cite
|
Sign up to set email alerts
|

Does working capital management affect firm profitability? Evidence from European Union countries

Abstract: PurposeThe paper aims to investigate the dynamic relationship between working capital management and firm profitability for a sample of firms from eight European Union (EU) countries for the period 2006–2015.Design/methodology/approachThe panel regression model is used in the study. Firm profitability is measured using the return on assets (ROA) ratio, whilst cash conversation cycle, financial leverage, size, tangibility and cash flow ratio are used as independent variables. The novelty of this study is the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…First of all, our findings denote that firms with shorter CCC have higher profitability as indicated by an estimated negative relationship. Moreover, in contrast to some previous contributions in which the relationship between CCC and firm profitability follows an inverted U-shaped pattern (see e.g., Deari et al, 2022;Altaf and Shah, 2018), our analysis suggests that such relationship is decreasing and convex, since the estimated coefficient related to CCC2 is positive and significant.…”
Section: Model Estimationcontrasting
confidence: 99%
See 3 more Smart Citations
“…First of all, our findings denote that firms with shorter CCC have higher profitability as indicated by an estimated negative relationship. Moreover, in contrast to some previous contributions in which the relationship between CCC and firm profitability follows an inverted U-shaped pattern (see e.g., Deari et al, 2022;Altaf and Shah, 2018), our analysis suggests that such relationship is decreasing and convex, since the estimated coefficient related to CCC2 is positive and significant.…”
Section: Model Estimationcontrasting
confidence: 99%
“…For example, Deari et al (2022) investigated the dynamic relationship between CCC and firm profitability for a sample of firms from eight EU countries for the period from 2006 to 2015 and find a positive relationship between WCM and profitability. Also, Prempeh and Peprah-Amankona (2020) establish a significant positive linear relationship.…”
Section: The Positive Relationship Between CCC and Firm Profitabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, some previous studies concluded a non-linear association between WCM measured by CCC and firm's FP. For instance, Deari et al (2022) examined the dynamic association between WCM and firm profitability measured by ROA using a sample of eight European Union countries covering 10 years from 2006 to 2015. The findings of the study indicated that there is a significant positive association between WCM and ROA.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%